Thermal Insulation, Antifreeze, and Anti-Drainage Technology for Tunnels in the Cold Area of Jinpen Bay - Tu Ha; Shengjun Liu; Libin Lin; Wei Liu; Hongwei Zhang; Lijun Sun; Xuemin Zhao (Buildings, 2023)
There are a large number of tunnels built in permafrost regions every year in China. When investigating the road tunnels that have been in operation in cold regions, it was found that most of these tunnels have various freezing damages. Therefore, in the design, construction, operation, and maintenance of tunnels in cold regions, there are still many technical problems that need to be solved urgently. Among them, the problems of heat preservation, anti-freezing, and anti-drainage are the key technical problems to determine whether the tunnels in cold regions are affected by freezing damage. The project was based on the completed highway tunnels in Inner Mongolia. Given a series of special problems faced by the construction and management of tunnels in cold regions, a large number of reference documents were consulted. This paper designed thermal insulation, antifreeze, and anti-drainage technology for tunnels in the cold area of Jinpen Bay. The research in this paper can effectively reduce the probability of the occurrence of tunnel freezing damage, ensure the safety of the long-term operation of the tunnel lining structure, and greatly reduce maintenance costs, which have good economic and social benefits.